The Fatal Allure of Extremist Logic: Syaifudin Zuhri and the July 17 Suicide Bombers - Sulastri Osman (2016)
Syaifudin Zuhri Djaelani was killed on October 9 during a police raid near Jakarta. Emerging details of how he recruited suicide bombers suggest that perhaps it is less the disaffected but more the intellectually curious who may be fodder for terrorist groups.